POST-PANDEMIC LEARNING DESIGN FOR ENGLISH STUDY PROGRAM - Siti Ermawati; Chyntia Heru Woro Prastiwi; Refi Ranto Rozak (Proceeding International Conference on Digital Education and Social Science, 2022)
During the COVID-19 pandemic, almost all students in higher education learned in online and hybrid modes. The results of evaluating the learning process during COVID-19 at IKIP PGRI Bojonegoro indicated that they were not ready for fully online learning and preferred the hybrid mode. However, when they were asked to choose between online or offline learning, they answered that they preferred offline learning due to several weaknesses in online learning and hybrid mode. This research analyzed the designs of post-pandemic learning at the English Study Program for three common supports, five core courses, and one institutional course given to the first semester students in the academic year of 2022/2023 by implementing project-based learning and case-based learning in a detailed explanation. The analyses focused on the course design, syntax, material, assessment, and lecturer role described in the syllabuses and lesson plans. Project-based learning and case-based learning as classroom management are designed to be implemented in the courses of Pancasila, Indonesian language, Religious Education, Educational Foundation, Speaking for Daily Context, Listening for Daily Context, General Vocabulary, Basic English Grammar, and Literal Reading. Both methods will engage students in learning and maximize their achievement in academic and life skills. Good classroom management with distinctive roles for lecturers and students will create active, effective, meaningful, and engaging learning